2011
DOI: 10.1007/s10557-010-6277-1
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Inhibits Homocysteine-Induced Dysfunction and Apoptosis in Endothelial Progenitor Cells

Abstract: AMPK activation inhibits eNOS down-regulation and Nox4-derived ROS accumulation induced by Hcy in EPCs, and may contribute to the protective effects of atorvastatin on endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…We found that AMPK activation negatively regulates the Nox4 protein expression and ROS production stimulated by HG. These observations are supported by numerous published studies showing that AMPK constitutes a physiological suppressor of ROS production via inhibition of NADPH oxidase activation and the expression of Nox subunits, including Nox4 (9,32,33,(65)(66)(67).…”
Section: Discussionsupporting
confidence: 64%
“…We found that AMPK activation negatively regulates the Nox4 protein expression and ROS production stimulated by HG. These observations are supported by numerous published studies showing that AMPK constitutes a physiological suppressor of ROS production via inhibition of NADPH oxidase activation and the expression of Nox subunits, including Nox4 (9,32,33,(65)(66)(67).…”
Section: Discussionsupporting
confidence: 64%
“…Rosiglitazone was reported to reduce glucose-induced oxidative stress (35) and stimulate nitric oxide synthesis (36) in endothelial cells via AMP-activated protein kinase (AMPK). AMPK inhibited homocysteine-induced apoptosis in EPCs and reduced reactive oxygen species (ROS) accumulation and endothelial nitric oxide synthase (eNOS) down-regulation (37). Therefore, we hypothesize that rosiglitazone may also attenuate TNF-α-induced EPC apoptosis via AMPK by reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 93%
“…Metformin is known to reduce both intracellular ROS levels and NADPH oxidase 4 expression (16). Furthermore, it has been reported that AMPK can stimulate the expression of HO-1 in macrophages and endothelial cells via the induction of nuclear factor-erythroid 2-related factor 2 (28).…”
Section: Discussionmentioning
confidence: 99%